2021
DOI: 10.1111/ane.13525
|View full text |Cite
|
Sign up to set email alerts
|

An Internet‐based study on the impact of COVID‐19 pandemic‐related lockdown on migraine in India

Abstract: Objectives To assess the impact of lockdown during the COVID‐19 pandemic on migraine patients in India on disease activity, healthcare accessibility, and quality of life (QoL). Materials & Methods This internet‐based survey study using a structured questionnaire was conducted from 27th April to 31st July 2020. Previous physician‐diagnosed migraine patients or those fulfilling any two of three clinical features (limitation of activities for >1 day, associated nausea or vomiting, and photophobia or phonophobia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Additionally, population studies conducted during the pandemic have found high migraine rates and increased symptoms (longer duration and intensity of the migraine episode) [ 26 ]. A worsening of the disease as a consequence of confinement has also been described in patients with migraine [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, population studies conducted during the pandemic have found high migraine rates and increased symptoms (longer duration and intensity of the migraine episode) [ 26 ]. A worsening of the disease as a consequence of confinement has also been described in patients with migraine [ 27 ].…”
Section: Discussionmentioning
confidence: 99%